Building the Evidence Base for the Prevention of Raw Milk-Acquired Brucellosis: A Systematic Review - Adetunji, Shakirat A.; Ramirez, Gilbert; Ficht, Allison R.; Perez, Ligia; Foster, Margaret J.; Arenas-Gamboa, Angela M. (Frontiers in Public Health, 2020)
Abstract Background: The scientific evidence of the health risks associated with the consumption of raw milk has been known for a long time. However, less clear is the impact of acquiring infectious diseases from raw milk consumption in the United States (US) due to incomplete reporting of cases and the complex factors associated with the sale and consumption of raw milk. Investigations of this current study focused on human brucellosis, one of the infectious diseases commonly acquired through the consumption of raw milk and products, and which continues to be a public health threat worldwide. Methodology: A qualitative systematic review of the sources of opinions that contribute to increased trend of raw milk sale and consumption in the US was conducted. Results: Interestingly, opinions about the sale of raw milk and/or the benefits arising from its consumption varied by US region, with the proportion of messages supporting raw milk consumption being highest in the Northeast compared to other US regions. Several evidence gaps and factors that possibly contribute to the increased prevalence of raw milk-acquired brucellosis were identified including inadequate monitoring of the raw milk sales process and lack of approved diagnostic methods for validating the safety of raw milk for human consumption. Conclusions: The unavailability of data specifying brucellosis cases acquired from raw milk consumption have precluded the direct association between raw milk and increased brucellosis prevalence in the United States. Nevertheless, the evidence gaps identified in this study demonstrate the need for intensified surveillance of raw-milk acquired infectious diseases including human brucellosis; establishment of safety and quality control measures for the process of selling raw milk; and design of an effective strategy for the prevention of raw milk-acquired infectious diseases including brucellosis. Overall, for the first time, this study has not only shown the gaps in evidence that require future investigations, but also, variations in the perception of raw milk consumption that may impact disease acquisition in different US regions.